Technological profile analysis in dairy companies: A case study (2023)
This paper presents the application of a Technology Management Methodology (TMM) in the analysis of the four M's (Machine, Methods, Management and Money) in twelve dairy companies located in the Colombian region of Meta. The application of the methodology was performed for the assessment of the technological and innovation profiles of the dairy companies. Multivariate statistical techniques were used in the structural analysis in order to identify major technological and innovation gaps in each company. Low technology processes were observed in this case study; however, these gaps can be considered as opportunities to promote technological innovation in the dairy companies by formulating action plans that include goals, strategies, and projects that contribute to the development of this area in the region under study. © Copyright 2017, AIDIC Servizi S.r.l.